2011
DOI: 10.1590/s0104-42302011000300012
|View full text |Cite
|
Sign up to set email alerts
|

Estudo prospectivo das complicações da Doença de Kawasaki: análise de 115 casos

Abstract: KD may progress with several complications even within months of the disease acute phase, eventually resulting in permanent sequelae. The earlier the diagnosis and therapeutic intervention with IV IgG administration are, the lower will be the occurrence of complications; the presence of thrombocytosis, anemia and elevated and extended inflammatory activity are risk factors for complication arising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
21

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 38 publications
0
26
1
21
Order By: Relevance
“…The clinical presentation is characterized by prolonged fever, polymorphous skin rash, nonpurulent conjunctival injection, extremity changes, oral mucosal changes, and cervical lymphadenopathy. The CNS involvement occurs in about 0.4% of children in the form of aseptic meningitis, meningoencephalitis, hypoperfused brain, ischemia, cerebral and cerebellar infarction, and subdural effusion [18, 19]. In the case of aseptic meningitis we must distinguish two different forms, first one being secondary to the disease and second one following IVIG administration [20].…”
Section: Kawasaki Diseasementioning
confidence: 99%
“…The clinical presentation is characterized by prolonged fever, polymorphous skin rash, nonpurulent conjunctival injection, extremity changes, oral mucosal changes, and cervical lymphadenopathy. The CNS involvement occurs in about 0.4% of children in the form of aseptic meningitis, meningoencephalitis, hypoperfused brain, ischemia, cerebral and cerebellar infarction, and subdural effusion [18, 19]. In the case of aseptic meningitis we must distinguish two different forms, first one being secondary to the disease and second one following IVIG administration [20].…”
Section: Kawasaki Diseasementioning
confidence: 99%
“…Knott, et al [5] found that 19 of 62 patients experienced SNHL with KD. Similarly, in the most recent and largest study of 115 KD patients by Alves, et al, [7] 33% had SNHL during the acute and subacute phases of the disease. In the present case, the patient's parents failed to identify the hearing problem early after discharge and brought him to our clinic 4 days later, when he failed to correctly recognize words, even when hearing his own speech.…”
Section: Discussionmentioning
confidence: 80%
“…KD is known to be associated with lesion of small-to-medium size arteries in most of the patients. But thoracic aortic aneurysms as the complication of KD are reported in 0.9% of patients with KD30) and aortic root dilatations are reported in 8% of patients with KD31). Also, there is another report that a 33 years-old man suffered from incomplete KD had a coronary artery bypass surgery because of the multiple-vessel coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%